Arquitetura de museus no Brasil contemporâneo: diálogos entre tempos e lugares - Ivo Renato Giroto (Midas: Museus e Estudos Interdisciplinares)
Since the beginning of the 21st century, Brazil has experienced a significant increase in the number and visibility of new museums. In the dialogue between architecture and art, architects have played a preponderant role, sometimes contributing to mutual appreciation, sometimes unbalancing the debate in favor of their creations. This article illustrates the rich panorama designed by the Brazilian museum architecture since 2000, highlighting the plurality of challenges and trends, and the web of cultural and generational relations that characterize such panorama. From a larger sample, five case studies are analysed, considering their importance and impact: Museu Oscar Niemeyer (2002), in Curitiba, by Oscar Niemeyer; Instituto Moreira Salles (2017), in São Paulo, by Andrade Morettin; Museu do Pão (2007), in Ilópolis (Rio Grande do Sul), by Brasil Arquitetura; Fundação Iberê Camargo (2008), in Porto Alegre, by Álvaro Siza Vieira; and Museu do Amanhã (2015), in Rio de Janeiro, by Santiago Calatrava. In this overview, stands out the peculiar coexistence between museums designed by architects from different generations and different cultural contexts. Icons of modern Brazilian architecture shared space with architects trained from the last quarter of the twentieth century, and together they witnessed a series of interventions in Brazil by internationally renowned architects.